2020
DOI: 10.3390/ani10081440
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variability in Response to Social Stress in Dairy Heifers

Abstract: Regrouping is associated with increased aggression, and disruption of time-budgets. Individuals vary in how well they cope with social stress. Our objective was to describe individual differences in agonistic behavior in dairy heifers after regrouping, and determine how time-budget and behavioral synchronization were affected by these coping strategies. A total of 30 heifers were individually regrouped at 5-months of age into stable groups of 12 unfamiliar animals. For 24 h, agonistic behaviors initiated and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…During the PRE period, most displacements were observed at the feed bunk, in line with previous work (Val-Laillet et al, 2008). The number of displacements increased in the POST period, and this corresponded to a higher proportion of displacements in the walking alley, with a lower proportion at the feed bunk in both groups, similar to recent findings in heifers (Nogues et al, 2020). Agonistic interactions in the walking alley were not directly associated with resource access, and thus the increase in this area was probably partly related to the formation of new dominance relationships (Kondo and Hurnik, 1990).…”
Section: Descriptive Resultssupporting
confidence: 91%
“…During the PRE period, most displacements were observed at the feed bunk, in line with previous work (Val-Laillet et al, 2008). The number of displacements increased in the POST period, and this corresponded to a higher proportion of displacements in the walking alley, with a lower proportion at the feed bunk in both groups, similar to recent findings in heifers (Nogues et al, 2020). Agonistic interactions in the walking alley were not directly associated with resource access, and thus the increase in this area was probably partly related to the formation of new dominance relationships (Kondo and Hurnik, 1990).…”
Section: Descriptive Resultssupporting
confidence: 91%
“…During the first 8 and last 8 h of regrouping, agonistic behaviors initiated or received by the focal heifer were continuously recorded (WV-CW504SP, Panasonic, Osaka, Japan). Behaviors were collected according to Nogues et al (2020). Briefly, these included displacements, replacements, avoidances, and fights (Table 1).…”
Section: Regrouping Induces Anhedonia-like Responses In Dairy Heifersmentioning
confidence: 99%
“…Although regrouping has been shown to cause negative physiological (Veissier et al, 2001) and behavioral effects in dairy cattle (von Keyserlingk et al, 2008;Nogues et al, 2020), little is known regarding the effects of this routine practice on the affective states of cattle. Stressors originating from the social environment may trigger negative affective states (Beery and Kaufer, 2015) and when applied as chronic stressors can induce depressive-like states in laboratory animals (Wang et al, 2017).…”
mentioning
confidence: 99%
“…Researchers have demonstrated that rats and pigs may react to social stressors by engaging in more aggressive behavior ( 40 , 41 ). Alternatively, Nogues et al ( 42 ) reported that some heifers avoided engaging in aggressive interactions, whereas, other heifers engaged in more aggressive interactions after regrouping. Interestingly, in that study, those heifers less willing to engage spent less time feeding and resting than the heifers that were more willing to engage in aggressive interactions to access important resources (i.e., feed bunk, lying stalls, waterers).…”
Section: Discussionmentioning
confidence: 99%